Polygyny and Exegesis Patriarchy of QS (4:3) In the Maqashidi Perspective - Nur Ida Fitria (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
Till now, QS (4:3) always been used as a legal tool to legitimize the practice of polygyny in patriarchal social construction. This problem is especially detrimental to women and their children. Even in a monogamous, many problems can arise, such as economic problems and balance in the relationship in main family, example between father and child, resulting in the problem of fatherlessness. Even more so in polygyny with many wives and children with different mothers. Thabathaba’i in Al-Mizan volume 7 page 206, he wrote: This verse 4:1 (as well as a few following ones which touch the subject of orphans and women) are a sort of prologue to prepare the minds for the rules of inheritance and marriage. The permissible number of wives that come in the third verse, has been mentioned here just as a side-line, taking advantage of the talk preceding it. The question was: Why the side-line issue then taking advantage too much and then cut off and leave the main issue about orphan and women rights and equity from God for them? Can we connected it with power in the men world that called patriarchy which fosters the ideology of polygyny? In fact, some interpreters have interpreted the QS (4:3) as a sharia command for men to practice polygyny. And with their patriarchal views then has an impact on dogmas that discredit women and have potential to give rise to violence and crimes that objectify women. That is why this topic is important to discuss and research, because the potential for violence is not limited to breaking women’s heart but also physical, sexual and even economic. Even at the height of violence, polygyny can also result in femicide, either directly or indirectly. This research uses a qualitative method by conducting literature analysis on books and scientific research journals. And through Tafsir Maqashidi’s scalpel, the author weaves new thoughts and interpretations regarding contemporary polygyny issues.